Contemporary thromboprophylaxis of trauma patients. Issue 6 (December 2016) - Van, Philbert Y.; Schreiber, Martin A.
Abstract : Purpose of review: The traumatically injured patient is at high risk for developing venous thromboembolism. Clinical practice guidelines developed by the American College of Chest Physicians and the Eastern Association for the Surgery of Trauma recognize the importance of initiating thromboprophylaxis, but the guidelines lack specific recommendations regarding the timing and dose of pharmacologic thromboprophylaxis. We review the literature regarding initiation of thromboprophylaxis in different injuries, the use of inferior vena cava filters, laboratory monitoring, dosing regimens, and the use of antiplatelet therapy. Recent findings: Use of pharmacologic thromboprophylaxis with invasive intracranial monitors is not associated with increased bleeding complications. The initiation of low-molecular-weight heparin (LMWH) prophylaxis 48 h postinjury in blunt solid organ injury is not associated with an increase in the rate of failed nonoperative management. Antiplatelet therapy in conjunction with LMWH may help to prevent venous thromboembolism. Summary: In the setting of blunt traumatic brain and solid organ injury, initiation of pharmacologic thromboprophylaxis 48 h after injury is not associated with increased bleeding complications. There is no consensus or clear data showing which dosing regimen of LMWH is most effective or whether routine laboratory measurements are beneficial for determining effective thromboprophylaxis.